The estimation trend of Malaysian SME occupational safety and health statistic - Nor Azma Rahlin; Munawar Mustafa; Abdul Halim Abdul Majid (Occupational Health and Safety Society of Nepal, 2018)
Background: In the current study, the mediating roles of safety climate and trust in the relations between leadership styles which are transformational and transactional and safety outcomes which are safety compliance and safety participation are studied. Methods and Material: 101 blue-collar workers from a company in Zonguldak were participated in the study. Results: The results showed that transactional leadership is strongly associated with safety climate. As predicted, transformational leadership is found to be significantly correlated with safety participation. Conclusions: Moreover, transactional leadership is strongly correlated with safety compliance. Both safety climate and trust showed significant correlation with both of the safety outcomes. The mediating roles of trust and safety climate within the relations between transactional leadership and safety compliance and transformational leadership and safety participation are also found